Self-perception of orofacial appearance: Brazil–Finland cross-national study - Campos, Lucas Arrais [UNESP]; Campos, Juliana Alvares Duarte Bonini [UNESP]; Kämäräinen, Minna; Silvola, Anna-Sofia; Marôco, João; Peltomäki, Timo (MJS Publishing, Medical Journals Sweden AB, 2022)
Objective: (i) To study the measurement invariance of Orofacial Esthetic Scale (OES) and Psychosocial Impact of Dental Aesthetics Questionnaire (PIDAQ), (ii) to compare the perception of orofacial appearance (OA) and (iii) to study the frequency of individuals who have sought or received aesthetic dental treatment between Brazil and Finland. Methods: This was a cross-sectional observational study with snowball non-probability sample selection. Students and staff from universities in Finland and Brazil were invited to participate. Data were collected online using a demographic questionnaire, OES and PIDAQ. The samples consisted of 3636 Finns (75.0% female; age: 32.0 years) and 1468 Brazilians (72.6% female; age: 33.2 years). The frequency of receiving aesthetic dental treatment was estimated. If configurational invariance was observed, cross-national measurement invariance was verified by multigroup analysis. When measurement invariance was attested, factor scores were compared using Welch’s t-test. Results: OES showed configurational and measurement invariance and no significant difference between the countries. Despite similarity in satisfaction with OA, 71.9% of Brazilians had received aesthetic dental treatment, while 59.4% of Finns had never sought such treatments. PIDAQ did not present configurational invariance between the countries. Conclusion: Although there is no difference in satisfaction with OA, seeking and receiving aesthetic dental treatment is significantly greater for Brazilians. Psychosocial impact of OA is perceived differently in the studied countries.
Keywords: Dental aesthetics; epidemiologic measurements; outcome measures; questionnaire